Baroque Spaces: the Flesh Bursts from Architecture - Figueiredo, Bruna Freitas (Opiniães, 2020)
We intend, in this text, to outline a reading of the plasticity, the textual fabrics, and the body and sculpture/architecture present in Chronicle of the murdered house (1959) and in Adriana Varejão's works. Understanding them as impasses in the face of the soul-body dichotomy and, then, of Christian morality, we suggest that their aesthetic proposals operate by tensioning this division through a convulsive beauty of language in which violence and resistance, repulsion and attraction seek an impossible reconciliation. The effect of this confrontation, thus, allows us to enter a field in which the Baroque appears, following Schollhammer's considerations, as a sensitive gesture on the readers, promoting the destabilization of their concepts as well as their subjectivity.